Bibliography of social science periodicals and monograph series: Hungary, 1947-1962. By Foreign Demographic Analysis Division, Bureau of the Census. Under grant from Office of Science Information Service, National Science Foundation (U.S. Department of Commerce, Bureau of the Census, 1964)
With indices.